Rapid Synthesis: Identifying Optimal Ways to Collect, Distill and Provide Efficient Access to Personal Health Information in Emergency Situations - Mahendren, M; Randhawa, H; Wilson, MG (My University, 2014)
An assessment of what is known about identifying optimal ways to collect, distill and provide efficient access to personal health information in emergency situations. The rapid synthesis was conducted to address a question posed by a health system policymaker or stakeholder to the McMaster Health Forum’s Rapid Response program.
Keywords: personal; health; information; emergency; situations